1980
DOI: 10.1136/jnnp.43.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials and contingent negative variation during treatment of multiple sclerosis with spinal cord stimulation.

Abstract: S U M M A R Y Cervical somatosensory evoked potentials, brainstem evoked potentials, visual evoked potentials, and the cerebral contingent negative variation were recorded in patients with definite multiple sclerosis before, during, and after spinal cord stimulation. Improvements were seen in the cervical somatosensory and brainstem evoked potentials but neither the visual evoked potential nor the contingent negative variation changed in association with spinal cord stimulation. The results indicate that spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Patients with neurological dis ease undergoing DCS are made fully aware that this is only an aid and certainly not a treatment or a cure for their neurological problems; a simi lar analogy is made to a hearing device for a patient having progressive nerve deafness. As to the neurophysiological mechanisms underlying DCS effective ness, our clinical findings support the theory that DCS increases the amount of background-afferent activity into a partially deafferented or weakened neuronal system [10,11,20]. DCS activates impulses orthodromically and antidromically in the dorsal columns (fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Patients with neurological dis ease undergoing DCS are made fully aware that this is only an aid and certainly not a treatment or a cure for their neurological problems; a simi lar analogy is made to a hearing device for a patient having progressive nerve deafness. As to the neurophysiological mechanisms underlying DCS effective ness, our clinical findings support the theory that DCS increases the amount of background-afferent activity into a partially deafferented or weakened neuronal system [10,11,20]. DCS activates impulses orthodromically and antidromically in the dorsal columns (fig.…”
Section: Discussionsupporting
confidence: 69%
“…DCS activates impulses orthodromically and antidromically in the dorsal columns (fig. I); orthodromic impulses ascend and subjectively cause the paresthesia of 'tingling', and supposedly augmenting higher brain stem centers [20] resulting in im provements in speech, swallowing, and eye coordination (tables II-V). Antidromic impulses supposedly travel into motoneuronal pools through the branched dorsal roots ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of possible [2,3,8,13,17] and questionable [16,24] ef fects of SCS in patients with upper m otor neuron dysfunction syn-drome, the recording of H reflex changes [11,14,21] and cervical so matosensory evoked potential changes [ 17] before and after continuous stimulation provide a better way of assessing the extent of any such ef fects. Furthermore, simultaneous electromyographic recording from several flexor and extensor leg muscles, while eliciting phasic and tonic stretch reflexes, vibratory-induced reflex responses, cutaneomuscular reflexes, and volitional control, along with polyelectromyographic re cording of activity during standing and walking, have been shown to be feasible techniques to monitor functional changes induced in pa tients by spinal cord stimulation [8], Finally, it has been demonstrated that upper thoracic SCS electrodes can be used to condition tendon jerk responses of the quadriceps [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in spinal cord stim ulation (SCS) for modification of im paired m otor activity have presented an opportunity for the clini cal researcher to observe [1, 4-7, 9, 12, 13, 15, 21-23], to record [13,17,21], and to study changes in abnorm al m otor activity in patients with upper m otor neuron dysfunctions [8]. However, from an experimental design point of view, the situation is rather complicated, due to the fact that the currently used stim ulation param eters require continuous ap plication o f the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IIIis et al [9] re ported that H-reflex inhibition by cutaneous afferents, found absent in patients with multiple sclerosis, reappeared on spinal cord stimulation. Lastly, Sedgwick et al [23] have shown a significant influence of spinal cord stimulation on cervical somatosensory-evoked potentials and on brain stem auditory-evoked potentials. Also of importance in our consi derations is the fact that the effects obtained through a short period of spinal cord stimulation may persist for hours after discontinuation of the stimuli.…”
Section: Introductionmentioning
confidence: 99%